Key Factors Leading to Program Selection: A Survey of Physician Assistant Program Interviewees. Issue 1 (March 2018) - Sierra, Talia; Forbes, Jennifer; Mirly, Alan; Domenech Rodríguez, Melanie M.
Abstract : Purpose: The purpose of this study was to determine which factors had the greatest influence on physician assistant (PA) interviewees' decision to choose a PA program to attend. The information in this article may assist PA programs in making their program more attractive to potential applicants and also may help applicants identify programs that will best fit their needs. Methods: Applicants who interviewed with a PA program were asked to rate 33 different influential factors when choosing a program to attend. Results: Respondents most highly endorsed quality of faculty and staff, first-time Physician Assistant National Certifying Examination pass rates, and morale of faculty and staff. Results varied by demographics, including marital status, age, and sex of respondent. Results also varied from pre-PA students. Conclusions: Although there are numerous factors involved in program selection, PA programs may want to focus on the quality and morale of their faculty and staff to help improve the likelihood of attracting and retaining the highest quality applicants.